Step
*
1
2
1
1
of Lemma
bag-summation-linear
1. T : Type
2. R : Type
3. add : R ⟶ R ⟶ R
4. mul : R ⟶ R ⟶ R
5. zero : R
6. f : T ⟶ R
7. g : T ⟶ R
8. minus : R ⟶ R
9. IsGroup(R;add;zero;minus)
10. Comm(R;add)
11. ∀[a,x,y:R].
      (((a mul (x add y)) = ((a mul x) add (a mul y)) ∈ R) ∧ (((x add y) mul a) = ((x mul a) add (y mul a)) ∈ R))
12. a : R
⊢ (a mul zero) = zero ∈ R
BY
{ Assert ⌜(a mul (zero add zero)) = (a mul zero) ∈ R⌝⋅ }
1
.....assertion..... 
1. T : Type
2. R : Type
3. add : R ⟶ R ⟶ R
4. mul : R ⟶ R ⟶ R
5. zero : R
6. f : T ⟶ R
7. g : T ⟶ R
8. minus : R ⟶ R
9. IsGroup(R;add;zero;minus)
10. Comm(R;add)
11. ∀[a,x,y:R].
      (((a mul (x add y)) = ((a mul x) add (a mul y)) ∈ R) ∧ (((x add y) mul a) = ((x mul a) add (y mul a)) ∈ R))
12. a : R
⊢ (a mul (zero add zero)) = (a mul zero) ∈ R
2
1. T : Type
2. R : Type
3. add : R ⟶ R ⟶ R
4. mul : R ⟶ R ⟶ R
5. zero : R
6. f : T ⟶ R
7. g : T ⟶ R
8. minus : R ⟶ R
9. IsGroup(R;add;zero;minus)
10. Comm(R;add)
11. ∀[a,x,y:R].
      (((a mul (x add y)) = ((a mul x) add (a mul y)) ∈ R) ∧ (((x add y) mul a) = ((x mul a) add (y mul a)) ∈ R))
12. a : R
13. (a mul (zero add zero)) = (a mul zero) ∈ R
⊢ (a mul zero) = zero ∈ R
Latex:
Latex:
1.  T  :  Type
2.  R  :  Type
3.  add  :  R  {}\mrightarrow{}  R  {}\mrightarrow{}  R
4.  mul  :  R  {}\mrightarrow{}  R  {}\mrightarrow{}  R
5.  zero  :  R
6.  f  :  T  {}\mrightarrow{}  R
7.  g  :  T  {}\mrightarrow{}  R
8.  minus  :  R  {}\mrightarrow{}  R
9.  IsGroup(R;add;zero;minus)
10.  Comm(R;add)
11.  \mforall{}[a,x,y:R].
            (((a  mul  (x  add  y))  =  ((a  mul  x)  add  (a  mul  y)))
            \mwedge{}  (((x  add  y)  mul  a)  =  ((x  mul  a)  add  (y  mul  a))))
12.  a  :  R
\mvdash{}  (a  mul  zero)  =  zero
By
Latex:
Assert  \mkleeneopen{}(a  mul  (zero  add  zero))  =  (a  mul  zero)\mkleeneclose{}\mcdot{}
Home
Index